Synthesis of Gold Nanoparticles Conjugated with Protein A: Towards the Application in Biosensors for Virus Detection - Huy, Tran Quang; Tuan, Mai Anh (Communications in Physics, 2011)
In this article, a facile and effective technique is described to prepare a complex of gold nanoparticles (GNPs)/protein A (PrA) for biosensors in virus detection. GNPs were synthesized by the reduction of tetrachloroauric (III) acid trihydrate using sodium ascorbate, and then coated with PrA via ultracentrifugation. The complex of GNPs/PrA was characterized using UV-vis spectroscopy and transmission electron microscopy. The immunogold labeling method of scanning electron microscopy was also used to verify the capacity for the detection and binding of GNPs/PrA to H$_{1}$N$_{1}$ influenza A virus particles. The results showed that GNPs were spherical, uniform shape, and approximately 10 nm in size. Noticeably, the complex of GNPs/PrA could detect and bind effectively to H$_{1}$N$_{1}$ influenza A virus particles by a large number of GNPs surrounded. The advantage of the complex of GNPs/PrA showed a highly potential application in biosensors with the improvement of the sensitivity and transducing signal for virus detection.